Teaching for learning mathematics - Sutherland, Rosamund 1947- (Open University Press McGraw-Hill, 2007)
Why do students find learning mathematics difficult? Can anything be done about this? What can we learn from mathematics lessons in which students are motivated to struggle with difficult mathematical ideas? How can teachers make sense of the research which is available, and use it to improve practice in real classrooms? This book explores the factors that influence young people's learning of mathematics. It uses a holistic, socio-culturally informed approach to show how all young people can be encouraged to engage with and learn mathematics. Rich examples from classroom practice are used to connect theory and practice. The role of mathematical tools, including information and communications technologies, is discussed. A key focus of the book is the link between teaching and learning, including different ways in which teachers can design and orchestrate mathematical learning environments. This important, accessible and relevant book is essential reading for student teachers of mathematics as well as all qualified mathematics teachers in secondary schools. This title explores the factors that influence young people's learning of mathematics. It uses a holistic, socio-culturally informed approach to show how all young people can be encouraged to engage with and learn mathematics